'Technically wrong leh': Leh as a feature of Singapore Colloquial English. Issue 4 (December 2019) - Botha, Werner
Abstract : There has been much discussion on the use of particles (also referred to as 'discourse particles' or 'pragmatic particles') as a key feature of Singapore English. Wong (2004) has pointed out that particles are essential in the Singapore speech community, and in order to pass as a functional member of the speech community a speaker needs to have a proficient knowledge of the meanings and functions of particles in spoken (and increasingly in texted) discourse. There is no doubt that the use of particles in Singapore Colloquial English is prevalent in the language use of speakers in Singapore, as attested by the numerous studies conducted on the topic since the 1970s (including Tongue, 1974; Richards & Tay, 1981; Kwan–Terry, 1978; Platt & Weber, 1980; Platt, Weber & Ho, 1983; Platt & Ho, 1989; Gupta, 1992; Wong, 2004, 2005; Wee, 2002, 2003, 2004, 2010; Liemgruber, 2016; Botha, 2018). Despite the fact that particles have been studied extensively, very few studies have investigated which particular particles can be considered prototypical in Singapore English in general, as well as more specifically in the vernacular speech of Singaporeans. Not only that, there appears still to be a lot we do not know about the functions and uses of many of these particles, specifically in the vernacular speech of Singaporeans.